ANALISIS YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK ORANG PRIBADI (Studi Pada Kantor Pelayanan Pajak Pratama Demak) - Mohklas, Mohklas; Pancawardani, Nurul Latifah (JAB (Jurnal Akuntansi & Bisnis), 2021)
Study analyze the perceived ease of use of e-filing, perceptions of the usefulness of using e-filing, taxpayer awareness and satisfaction with the use of e-filing that affect individual taxpayer compliance at KPP Pratama Demak. Population in this study are individual taxpayers who are registered at KPP Pratama Demak. Samples were taken as many as 100 respondents using the Nonprobability sampling method, namely Accidental Sampling by taking sample members from the population based on chance and deemed suitable by the researcher. Data analysis used multiple linear regression analysis with SPSS software version 22. While data collection using questionnaires. Results showed that the perception of the ease of using e-filing and taxpayer awareness had a positive and significant effect on taxpayer compliance, but the perception of the usefulness of using e-filing and satisfaction with the use of e-filing had no effect on individual taxpayer compliance at KPP Pratama Demak.Â Keywords: Perception of Convenience, Perception of Benefit, Taxpayer Awareness, Satisfaction with E-filing Use and Taxpayer Compliance